A relação humano-natureza no Quilombo: fauna silvestre e preservação das tradições ecológicas culturais na Comunidade Quilombola de Jacarequara, município de Santa Luzia do Pará - PEREIRA, Ana Beatriz da Conceição (2024)
Quilombola communities play an important role in society. Especially when it comes to preserving values and identity and conserving biodiversity, as quilombos are historical sites with significant ecological and cultural diversity as part of humanity's heritage. Through these traditions, it is possible to recognize knowledge and practices that are still present, even in the face of threats to their permanence manifested within the territories. This research is a study carried out in the Quilombo of Jacarequara, in the municipality of Santa Luzia do Pará, between December 2019 and December 2023, with the aim of expanding studies on the relationship between human beings and nature using a cultural ecology approach. The results were collected through participant observation and semi-structured interviews with residents of the Quilombo. The research was conducted through dialogues with the older members of the community, those who have the knowledge and experience from the past. Subsequently, discussions were held with the younger residents who still hunt, and who are seen as the owners of the practice of capturing wild animals. Finally, an educational event was organized at the school to make the research interact with the teaching of younger generations. According to the oldest residents, some species were hunted in the past for food, such as: armadillo, guariba, monkey, coati, caititu, peccary, deer, tapir, paca, agouti, jabuti, caiman, curassow and jacu. Game meat was not sold, as it was only used for subsistence. One of the interviewees said that these animals have disappeared, but other residents indicate where some mammals and birds occur, as well as the methods of capture they use when hunting. The fauna is still concentrated in the remaining forested areas, mainly on the banks of the Guamá river, the Jacarequara Grande river and the Jacarequarazinho stream. Among mammals, the following are currently mentioned: armadillo (more than one species), monkey, coati, caititu, deer, paca, agouti, capybara, among others. Parrots, arãncuã, curassows, jacú and jatuacú are also birds mentioned in the interviews. The children at the school showed interest in and acceptance of the pedagogical action around local biodiversity, from which it was possible to bring together the content of the Sciences discipline and the local context. It can be considered that, in general, there is an awareness in the community of the need to respect the rivers, their riparian forests and the associated wildlife. However, the older residents suggest that there has been a serious loss of the traditional knowledge that guaranteed healthier relations between the community and the natural environment. For this reason, they have been working cooperatively on projects involving agroecology, biocultural memory and quilombola identity.